Faktor yang Memengaruhi Keputusan Pembelian Pupuk Organik Cair Merek Jimmy Hantu di Toko BTA - Alifia, Salma; Hapsari, Hepi; Setiawan, Iwan (Universitas Galuh, 2024)
The increasing number of human population encourages the fulfillment of food security and can be supported by the application of green sustainable agriculture. One way of implementing green sustainable agriculture is by using liquid organic fertilizer. However, the use of organic fertilizers are still not massive and the sales are relatively low. This study aims to analyze the factors that influence the purchase of Jimmy Hantu liquid organic fertilizer at Bintang Tani Abadi (BTA) store Serang City. This study used quantitative methods with an explanatory survey that took data from 65 respondents. Data analysis using descriptive statistical analysis and SEM-PLS. The result showed that cultural, social, personal, and psychological factors had positive relationship to purchasing decision. However, product attributes do not have a positive relationship with purchase decision of JH-LOF at BTA store Serang City.